(untitled) (Indian Journal of Child Health, 2024)
Heiner Syndrome is an unusual form of pulmonary hemosiderosis mostly caused by cow milk. It presents as iron deficiency anemia,and hypoproteinemia. This clinical case describes a female infant with failure to thrive presenting with cough, low grade fever , fastbreathing with refusal to feed. On examination severe anemia with congestive cardiac failure was found, the cause of which wa sevaluated. Chest X ray showed bilateral fluffy infiltrates mimicking pneumonia. Investigations revealed microcytic hypochromicanemia with normal corrected reticulocyte count. Iron deficiency anemia (IDA) was diagnosed. However, the etiology of bilater alfluffy lung infiltrates could not be established in this child. Hence Broncho Alveolar Lavage (BAL) for hemosiderin ladenmacrophages and immunoglobulin for cow milk precipitin was done to establish the diagnosis.